Preservation Strategy of Putar-miring Technique for Women (Case Study: Sentra Gerabah Pagerjurang, Klaten, Central Java) - Reza Aulia Akbar; Faizal Putra Budimas; Sangki Purabaya; Lantip Trisunarno (IPTEK Journal of Proceedings Series, 2019)
Sentra Gerabah Pagerjurang is one of the tourism villages in Klaten, which is known for the existence of pottery production using putar-miring techniques and craftswomen culture. The historical of putar-miring techniques and craftswomen make traditional pottery products are unique and high value to market, so that economic income and community welfare have increased. However, it was found that 73% of craftswomen didn’t realize that the historical values had a significant impact on people's welfare. Therefore, if people’s economic income decreases, culture existence will disappear. This research aims to formulate historical and cultural preservation strategies for putar-miring techniques and craftswomen. This research is a type of qualitative research conducted by in-depth interview, determining variables using Content Analysis, formulating strategies with SWOT analysis based on 5M+1E aspect, Community Total Led Sanitation (CLTS), as well as selecting the best preservation strategies using the Multi-Criteria-Decision-Making method. Based on this research, it can be concluded that there are six preservation strategies ranking through putar-miring techniques for women, namely: 1) Utilization of government land grants, 2) Giving historical education, culture, and economics of putar- miring technique, 3) Center of pottery developments as a tourism village, 4) Pottery production system developments, 5) Craftsmen and craftswomen training, and 6) Advocacy and negotiation government regulations